PENERAPAN MODEL SIKLUS BELAJAR 7E DENGAN PENDEKATAN JELAJAH ALAM SEKITAR (JAS) UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA MTS DARUL HIKMAH PEKANBARU KELAS VIIIB4 PADA MATERI SISTEM KEHIDUPAN TUMBUHAN - Sakina, Nurul; Wulandari, Sri; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aim of this research was to improve activity and learning result student through the application of models learning cycle 7E with approach to explore nature in class VIIIB4 IPA MTs Darul Hikmah Pekanbaru on system of life plant concepts. This research is action research conducted in two cycles in March until May 2016. The subjects were students of class VIIIB4 IPA MTs Darul Hikmah Pekanbaru, amounting to 30 people men. Parameter research is activities, learning result student consisting of absorption and mastery learning and. The average of students' learning activities in the first cycle is 77,12 % with sufficient category and the second cycle increased to 85,05 % with the very good category. Learning result student based on the average absorption of students in the first cycle is 79,33 and the second cycle increased to 86,67. Mastery learning students in the first cycle is 73.33% and the second cycle increased to 93,33%. From the results of this research concluded that the application of models learning cycle 7E with approach to explore nature can increase the activity and learning result student in class VIIIB4 MTs Darul Hikmah Pekanbaru on system of life plant concepts.Keywords : Model learning cycle 7E, approach to explore nature, activity, learning result student